Cheer Challenge - Jake Maddox (Stone Arch Books, 2008)
Amanda has always dreamed of being captain of a cheerleading squad, and this year, she is! But she soon realizes that being captain is harder than she thought. Not only does she have to lead the squad, she has to inspire them, and that$1 (Bs hard work.s
Keywords: Sport Stories -- Sport Stories